Rethinking class size : the complex story of impact on teaching and learning - Blatchford, Peter; Russell, Anthony, 1942- (UCL Press, 2020)
In Rethinking Class Size, the world's leading researchers into class size effects counter the dominant view that class size has no impact on pupil outcomes. Peter Blatchford and Anthony Russell reveal the influence of class size on all relationships and interactions in the classroom. They develop a new social pedagogical model of how class size influences work, and identify policy conclusions and implications for teachers and schools. The book is an invaluable contribution to the international debate on class sizes.